Factors associated with non-active retinal capillary density as measured with Confocal Scanning Laser Doppler Flowmetry in an elderly population: the Thessaloniki Eye Study (TES). Issue 9 (29th November 2019) - Dervenis, Nikolaos; Harris, Alon; Coleman, Anne L; Wilson, M Roy; Founti, Panayiota; Yu, Fei; Siesky, Brent; Anastasopoulos, Eleftherios; Pappas, Theofanis; Koskosas, Archimidis; Kilintzis, Vassilis; Topouzis, Fotis
Abstract : Purpose: To identify factors associated with retinal capillary density as measured with Confocal Scanning Laser Doppler Flowmetry (Heidelberg retina flowmeter (HRF)) in the Thessaloniki Eye Study (TES). Methods: Participants of the TES (age ≥60 years, cross-sectional population-based study) were assessed for active capillary density in the superior and inferior peripapillary retina using the HRF. Pixel-by-pixel analysis was performed to quantify the percentage of zero flow pixels (ZFPs; surrogate for % retinal area with non-active capillaries). Multivariable regression analyses were performed to assess the association of non-active vascular density with ophthalmic and systemic variables. Glaucoma, late age-related macular degeneration and diabetic retinopathy subjects were excluded. Results: 1189 subjects were included in the analysis. Older age (per year) was associated with higher percentage of ZFP in both the superior (slope estimate (SE)=0.0020) and the inferior (SE=0.0019) peripapillary retina (p<0.0001). History of migraine was associated with lower percentage of ZFP (SE=−0.0166) compared with no history of migraine in the superior peripapillary retina only (p<0.05). Higher intraocular pressure ((IOP) per mm Hg) and height (per cm) were associated with higher percentage of ZFP in the inferior peripapillary retina only (SE=0.0012, p<0.05 and SE=0.0005, p<0.05, respectively). The group consuming vegetables one to three times per week compared with the group consuming vegetables at least once a day had higher percentage of ZFP only in the inferior peripapillary retina (SE=0.0080, p<0.05). Conclusion: At a population level, our study revealed associations of older age, higher IOP and taller height with lower active retinal capillary density and of migraine with higher capillary density. Looking further into these associations may provide insight into disease mechanisms.